FRASA DALAM BAHASA TAE’ (Phrase in Tae’ Language) - Asri Nur Hidayah (SAWERIGADING, 2017)
This research aims to describe the phrase in Tae’ language. Data obtained from native speakers and oral literature of Tae’. Data gathered by using of recording and noting techniques, and also using an instrument.Data analyzed by using structural analysis through qualitative approach. The results show that there are seven classes of phrases in Tae’ language, namely 1) adjective phrase, 2) noun phrase, 3) verb phrase, 4) pronoun phrase, 5) numeral phrase, 6) preposition phrase, and 7) adverb phrase. Based on the elemental context on the constituents, the phrases are distinguished from endocentric and exocentric phrase. The characteristics of this phrase located to the adjective phrase, verb phrase, preposition phrase, and numeral phrase. The adjective phrase (A + Adv) beccu’ siapi → beccu’ siapi ‘small still’ means ‘still small’ thus its constituent to be Adv (still) + Adj (small). Verb phrase (V + Prep) latumangi + duka “will cry too” changed its constituent to be FV + Prep. Preposition phrase with its constituent (N) bulan ‘month’ + (Prep) lendupa ‘since then’; month since then; since last month (Prep) + (N). The same thing happens to the phrase which is structured Num + Prep, duangallopa + lendu → duangallopa lendu ‘two days ago since; since two days ago in accordance with the constituent of Indonesian language Prep + Num. Phrase occupies the function S, P, O, Pel, K. Its semantic role is the experiencer, conveying a situation, and stating of place.AbstrakPenelitian ini bertujuan untuk mendeskripsikan frasa dalam bahasa Tae’. Data diperoleh dari penutur asli dan sastra lisan Tae’. Data dikumpulkan dengan menggunakan teknik menyimak dan mencatat, serta menggunakan instrumen. Data dianalisis dengan menggunakan analisis struktural melalui pendekatan kualitatif. Hasil penelitian menunjukkan bahwa ada tujuh kelas frasa dalam bahasa Tae’, yaitu 1) frasa adjektiva, 2) frasa nomina, 3) frasa verba 4) frasa pronomina, 5) frasa numeralia, 6) frasa preposisi, dan 7) frasa adverbia. Berdasarkan hubungan unsur dalam struktur, frasa dibedakan atas frasa endosentris dan frasa eksosentris. Karakteristik frasa terletak pada frasa adjektiva, frasa verba, frasa preposisi, dan frasa numeralia. Frasa adjektiva (A + Adv) beccuq + siapi →beccuq siapi ‘kecil masih’ bermakna ‘masih kecil’ sehingga strukturnya menjadi Adv (masih) + Adj (kecil). Frasa verba (V +Prep) latumangi + duka ‘mau menangis juga; berubah strukturnya menjadi FV +Prep. Frasa preposisi dengan struktur (N) bulan ‘bulan’ + (Prep) lendupa ‘sejak lalu’; bulan sejak lalu; sejak bulan lalu (Prep) + (N). Hal ini sama dengan frasayang berstruktur Num + Prep, duangallopa + lendu → duangallopa lendu ‘dua hari lalu sejak; sejak dua hari yang lalu’ sesuai dengan struktur bahasa Indonesia Prep + Num. Frasa menduduki fungsi S, P, O, Pel, K. Peran semantisnya adalah pengalam, menyatakan keadaan, dan keterangan tempat.